Cryoablation vs radiofrequency ablation for the treatment of renal cell carcinoma: a meta-analysis of case series studies - El Dib, Regina [UNESP]; Touma, Naji J.; Kapoor, Anil (Wiley-Blackwell, 2012)
OBJECTIVETo determine the current status of the literature regarding the clinical efficacy and complication rates of cryoablation vs radiofrequency ablation in the treatment of small renal tumours.METHODSA review of the literature was conducted. There was no language restriction. Studies were obtained from the following sources: MEDLINE, EMBASE and LILACS.Inclusion criteria were (i) case series design with more than one case reported, (ii) use of cryoablation or radiofrequency ablation, (iii) patients with renal cell carcinoma and, (iv) outcome reported as clinical efficacy.When available, we also quantified the complication rates from each included study.Proportional meta-analysis was performed on both outcomes with a random-effects model. The 95% confidential intervals were also calculated.RESULTSThirty-one case series (20 cryoablation, 11 radiofrequency ablation) met all inclusion criteria.The pooled proportion of clinical efficacy was 89% in cryoablation therapy from a total of 457 cases. There was a statistically significant heterogeneity between these studies showing the inconsistency of clinical and methodological aspects.The pooled proportion of clinical efficacy was 90% in radiofrequency ablation therapy from a total of 426 cases. There was no statistically significant heterogeneity between these studies.There was no statistically significant difference regarding complications rate between cryoablation and radiofrequency ablation.CONCLUSIONSThis review shows that both ablation therapies have similar efficacy and complication rates.There is urgency for performing clinical trials with long-term data to establish which intervention is most suitable for the treatment of small renal masses.
Keywords: cryoablation; radiofrequency ablation; small renal tumours; meta-analysis of cases series studies